Design and Implementation of Enterprise-Level Network Disk in Power System. Issue 3 (February 2020) - Qian, Lin; Yu, Jun; Zhu, Guangxin; Xie, Ruocheng; Chen, Zhengbo; Mei, Zhu; Wang, Lin; Pang, Hengmao; Xu, Mingjie; Chen, Haiyang
Abstract: This system is an Enterprise-Level information sharing platform based on browser/server mode (B/S), page frame stand tools in hypertext preprocessor language package. It consists of the user management module, file management module, friend's management module, information management module and administrator module. The system can provide in LAN users to more quickly and more convenient to share pictures, file upload and download, and make them in the Internet which is not restricted by time and space. Through the implementation of the system, the information exchange between users is promoted, the user's free access is realized, the operation becomes simpler, the efficiency of information interaction between the employees of the enterprise is improved, and the work efficiency is improved.